OpenCV 3.0 computer vision with Java : create multiplatform computer vision desktop and web applications using the combination of OpenCV and Java /: create multiplatform computer vision desktop and web applications using the combination of OpenCV and Java. (2015) - Lelis Baggio, Daniel
No abstract available